CORRUPTION AND MONEY LAUNDERING IN BRAZIL: THE SIGNIFICANT IMPACT ON THE ECONOMY (CIPEEX, 2024)
The aim of this work is to investigate the ramifications of corruption and moneylaundering in the Brazilian economy, analyzing how these crimes impact economicgrowth, resource distribution, investor confidence, and financial stability. Additionally,efforts were made to identify effective strategies to combat and prevent thesepractices, contributing to the strengthening of the Rule of Law and the advancementof institutional transparency. To conduct this research, a qualitative approach wasemployed for data collection and analysis. The choice of qualitative methodology isappropriate as it allows for a in-depth understanding of complex social phenomenasuch as corruption, money laundering, and their impact on the Brazilian economy.While measures to combat and prevent corruption and money laundering have beenidentified, the literature also highlighted the need for further research to assess theeffective impact of these policies and specific measures. Furthermore, it is essential todelve deeper into the analysis of the regional and sectoral implications of corruptionand money laundering in the Brazilian economy. However, significant challengespersist, including the effectiveness of law enforcement, resource capacity, institutionalindependence, and impunity in some cases. The slowness of the judicial system andthe need to ensure the continuity and strengthening of these measures are alsopressing issues. Finally, corruption and money laundering have a profound anddetrimental impact on the Brazilian economy. Progress in the fight against these issuesrequires a continued commitment to the effective enforcement of laws, institutionaltransparency, and the strengthening of oversight institutions. Furthermore, promotinga culture of integrity and ethics in all sectors of Brazilian society is necessary. Only inthis way can the country move towards a fairer, more transparent, and prosperousfuture.